Communal Knowledge and the Beatific Vision - Cockayne, Joshua (TheoLogica, 2018)
In this paper, I will consider what role, if any, our communion with the saints plays in our knowledge and communion with God. By considering recent work on the epistemology of personal knowledge and epistemology of religious ritual, I argue that our communion with the saints in some way enhances our knowledge of God. This conclusion has implications for our understanding of the beatific vision. According to Thomas Aquinas, those who are saved will receive a vision of the divine essence and thereby come to perfect knowledge of God. In attaining this perfect knowledge, Aquinas maintains, a human being will be perfectly happy. Thus, on Aquinas's picture of the doctrine, communion with the saints is not necessary for perfect happiness or perfect knowledge of God. I suggest that there are two solutions to this problem. First, following Christopher Brown, we must say that whilst perfect happiness cannot be improved upon it can be somehow more extensive. Or, secondly, we must say that, in some sense, the beatific vision is communal in nature. Whilst God remains the object and source of perfect happiness on such an account, our vision of God is a shared vision.